Chimeric antigen receptor T-Cell therapy for breast cancer: current status, challenges and future perspectives - Kui Liu; Qi Sun; Shanmei Du (Journal of Translational Medicine, 2026)
Abstract Background Breast cancer is the most common female malignancy worldwide, and its molecular heterogeneity and immunosuppressive tumor microenvironment (TME) severely limit the efficacy of conventional therapies. Although chimeric antigen receptor T-cell (CAR-T) therapy has revolutionized hematologic malignancy treatment, it faces bottlenecks in breast cancer, including antigen heterogeneity/escape, poor subtype adaptation, and TME-mediated immunosuppression, creating an urgent need for optimized strategies to bridge the translational gap between CAR-T engineering and breast cancer biology. Main body Following a "bottleneck-solution" logic, this review dissects three core barriers to CAR-T efficacy in breast cancer: antigen-related issues (heterogeneity, escape, on-target off-tumor toxicity), subtype adaptation barriers (distinct immune/molecular features of Luminal A/B, HER2-positive and triple-negative breast cancer [TNBC], and research bias), and TME constraints (immunosuppressive cells, physical/metabolic barriers, overexpressed immune checkpoints). It elaborates three interconnected optimization strategies: subtype-specific precision CAR design, dual-target CAR engineering (tandem, parallel, logic-gated SynNotch CARs), and multi-dimensional TME modification (immunosuppressive cell clearance, physical/metabolic remodeling, immune signaling modulation). The review also summarizes early clinical trial progress, showing manageable safety and preliminary efficacy in HER2-positive and TNBC patients, and analyzes key clinical translation challenges (safety management, manufacturing scalability, efficacy durability) with targeted coping strategies. Finally, it explores next-generation technologies, including novel effector cell therapies (CAR-NK, CAR-M, nanobody-mediated CAR-T), in vivo CAR engineering, and AI-guided personalized design. Conclusions CAR-T therapy has evolved into a clinically viable immunotherapeutic strategy for breast cancer, with significant progress in addressing core bottlenecks via precision engineering, combination therapies and technological innovation. Despite remaining challenges in manufacturing, efficacy durability and accessibility, the integration of synthetic biology, computational immunology and precision oncology lays a solid foundation for further optimization. Deepening subtype-targeted therapy, upgrading CAR engineering/manufacturing platforms, optimizing combination regimens, and advancing clinical translation and accessibility will be core research directions. With collaborative efforts across academia, industry and regulatory bodies, CAR-T therapy is expected to become a standard treatment for breast cancer, especially aggressive subtypes, and bring durable remissions and improved survival for patients globally.